2021
DOI: 10.1101/2021.08.27.457908
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tightly-coupled inhibitory and excitatory functional networks in the early visual cortex

Abstract: Intracortical inhibition plays a critical role in shaping activity patterns in the mature cortex. However, little is known about the structure of inhibition in early development prior to the onset of sensory experience, a time when spontaneous activity exhibits long-range correlations predictive of mature functional networks. Here, using calcium imaging of GABAergic neurons in the early ferret visual cortex, we show that spontaneous activity in inhibitory neurons is already highly organized into distributed mo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Prior work has suggested that in early development, when intracortical horizontal connections are thought to be primarily short-range (Durack and Katz, 1996), recurrent local circuits can give rise to distributed and modular correlations through self-organizing mechanisms (Smith et al, 2018;Mulholland et al, 2024). In such theoretical models (von der Malsburg, 1973;Ernst et al, 2001), this modular structure arises through the interaction of local excitation and lateral inhibition (LE/LI), and predicts a tight coupling of activity in excitatory and inhibitory populations, which has been observed in V1 in early development (Mulholland et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior work has suggested that in early development, when intracortical horizontal connections are thought to be primarily short-range (Durack and Katz, 1996), recurrent local circuits can give rise to distributed and modular correlations through self-organizing mechanisms (Smith et al, 2018;Mulholland et al, 2024). In such theoretical models (von der Malsburg, 1973;Ernst et al, 2001), this modular structure arises through the interaction of local excitation and lateral inhibition (LE/LI), and predicts a tight coupling of activity in excitatory and inhibitory populations, which has been observed in V1 in early development (Mulholland et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In such theoretical models (von der Malsburg, 1973;Ernst et al, 2001), this modular structure arises through the interaction of local excitation and lateral inhibition (LE/LI), and predicts a tight coupling of activity in excitatory and inhibitory populations, which has been observed in V1 in early development (Mulholland et al, 2021). Such LE/LI mechanisms appear to be engaged in early V1 where unstructured optogenetic activation gives rise to modular cortical activity (Mulholland et al, 2024). It is possible that a similar mechanism may operate in early development in other cortical regions, although this remains to be tested.…”
Section: Discussionmentioning
confidence: 99%